Cesium Ion‐Mediated Microporous Carbon for CO2 Capture and Lithium‐Ion Storage. Issue 2 (16th December 2020) - Lee, Hyeon Jeong; Ko, Dongah; Kim, Joo‐Seong; Park, Youngbin; Hwang, Insu; Yavuz, Cafer T.; Choi, Jang Wook
Abstract: Activated carbon has been used in a wide range of applications owing to its large specific area, facile synthesis, and low cost. The synthesis of activated carbon mostly relies on potassium hydroxide (KOH)‐mediated activation which leads to the formation of micropores (<2 nm) after a washing step with acid. Here we report the preparation of activated carbon with an anomalously large surface area (3288 m 2  g −1 ), obtained by employing an activation process mediated by cesium (Cs) ions. The high affinity of the carbon lattice for Cs ions induces immense interlayer expansion upon complexation of the intercalant Cs ion with the carbon host. Furthermore, the Cs‐activation process maintains the nitrogen content of the carbon source by enabling the activation process at low temperature. The large surface area and well‐preserved nitrogen content of Cs‐activated carbon takes advantage of its enhanced interaction with CO2 molecules (for superior CO2 capture) and lithium ions (for improved Li ion storage), respectively. The present investigation unveils a new approach toward tuning the key structural properties of activated carbon; that is, controlling the affinity of the carbon host for the intercalant ion when they engage in complex formation during the activation process. Abstract : Cesium ion‐mediated activated carbon is reported as replacement for conventional potassium ion‐mediated activated carbon. The high affinity of the carbon host for cesium ions induces immense interlayer expansion of the carbon structure upon complexation, resulting in an enormous specific surface area of 3288 m 2  g −1 . Facile pore generation enhances the performance of Cs‐activated carbon in terms of both CO2 capture and Li‐ion storage.